2001
DOI: 10.1128/iai.69.12.7955-7958.2001
|View full text |Cite
|
Sign up to set email alerts
|

Innate Resistance toBabesiaInfection Is Influenced by Genetic Background and Gender

Abstract: Infection of severe combined immunodeficient mice with Babesia sp. strain WA1 was studied to assess the contributions of innate and adaptive immunity in resistance to acute babesiosis. The scid mutation showed little effect in genetically susceptible C3H mice and did not decrease the inherent resistance of C57BL/6 mice to the infection, suggesting that innate immunity plays a central role in determining the course of Babesia infection in these strains. In contrast, the scid mutation dramatically impaired resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…Moreover, the susceptibility and the outcomes of the infection may be influenced by the genetic backgrounds of the mice; for instance, the A/J, C3H, and BALB/c mouse strains are highly susceptible to infection, whereas C57BL/6 mice are resistant to rodent babesiosis. This difference is most probably dependent on the innate immunity mechanisms (1). The global emergence of human babesiosis has spurred an interest in developing effective strategies for a better management and control of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the susceptibility and the outcomes of the infection may be influenced by the genetic backgrounds of the mice; for instance, the A/J, C3H, and BALB/c mouse strains are highly susceptible to infection, whereas C57BL/6 mice are resistant to rodent babesiosis. This difference is most probably dependent on the innate immunity mechanisms (1). The global emergence of human babesiosis has spurred an interest in developing effective strategies for a better management and control of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…As to TBD, the response is known to be under multi-factorial regulation (Horin, 1998;Aguilar-Delfin et al, 2001). As highlighted in the above section 4, the phenomenon of tolerance is a broad-based one and possibly not unrelated to the erythropoietic system in different sheep breeds or to the haemoglobin genetic systems (Pieragostini et al, 2003;Pieragostini et al, 2006).…”
Section: Response To Anaplasma Ovis Infection In Experimentally Infecmentioning
confidence: 99%
“…strain WA1 infection in C57BL/6 mice, with males being more resistant than females. 23 Conversely, Hughes and Randolph reported that testosterone causes prolonged and more intense B. microti infection. 27 Thus, these apparently conflicting studies have failed to clearly define the impact of sex-based differences on parasitemia in and clinical symptoms of B. microti infection.…”
mentioning
confidence: 99%
“…strain WA1, and susceptible mouse models. [23][24][25][26][27][28][29] Aguilar-Delfin and others reported a sex-related influence on resistance to acute Babesia sp. strain WA1 infection in C57BL/6 mice, with males being more resistant than females.…”
mentioning
confidence: 99%